Final Laurentide ice-sheet deglaciation and Holocene climate-sea level change. (15th November 2016) - Ullman, David J.; Carlson, Anders E.; Hostetler, Steven W.; Clark, Peter U.; Cuzzone, Joshua; Milne, Glenn A.; Winsor, Kelsey; Caffee, Marc
Abstract: Despite elevated summer insolation forcing during the early Holocene, global ice sheets retained nearly half of their volume from the Last Glacial Maximum, as indicated by deglacial records of global mean sea level (GMSL). Partitioning the GMSL rise among potential sources requires accurate dating of ice-sheet extent to estimate ice-sheet volume. Here, we date the final retreat of the Laurentide Ice Sheet with 10 Be surface exposure ages for the Labrador Dome, the largest of the remnant Laurentide ice domes during the Holocene. We show that the Labrador Dome deposited moraines during North Atlantic cold events at ∼10.3 ka, 9.3 ka and 8.2 ka, suggesting that these regional climate events helped stabilize the retreating Labrador Dome in the early Holocene. After Hudson Bay became seasonally ice free at ∼8.2 ka, the majority of Laurentide ice-sheet melted abruptly within a few centuries. We demonstrate through high-resolution regional climate model simulations that the thermal properties of a seasonally ice-free Hudson Bay would have increased Laurentide ice-sheet ablation and thus contributed to the subsequent rapid Labrador Dome retreat. Finally, our new 10 Be chronology indicates full Laurentide ice-sheet had completely deglaciated by 6.7 ± 0.4 ka, which re quires that Antarctic ice sheets contributed 3.6–6.5 m to GMSL rise since 6.3–7.1 ka. Highlights: New 10 Be surface exposure chronology of final Laurentide ice-sheet retreat. Laurentide ice deposited moraines during century-scale North Atlantic cold events. Rapid ice-volume loss shortly after the removal of ice over Hudson Bay. Regional climate model shows an open Hudson Bay as an additional heat source. Laurentide deglaciation constrains Antarctic Holocene sea-level rise contribution.